RAS-protein activation but not mutation status is an outcome predictor and unifying therapeutic target for high-risk acute lymphoblastic leukemia - Koschut, David (Springer Nature, 2021)
Leukemias are routinely sub-typed for risk/outcome prediction and therapy choice using acquired mutations and chromosomal rearrangements. Down syndrome acute lymphoblastic leukemia (DS-ALL) is characterized by high frequency of CRLF2-rearrangements, JAK2-mutations, or RAS-pathway mutations. Intriguingly, JAK2 and RAS-mutations are mutually exclusive in leukemic sub-clones, causing dichotomy in therapeutic target choices. We prove in a cell model that elevated CRLF2 in combination with constitutionally active JAK2 is sufficient to activate wtRAS. On primary clinical DSALL samples, we show that wtRAS-activation is an obligatory consequence of mutated/hyperphosphorylated JAK2. We further prove that CRLF2-ligand TSLP boosts the direct binding of active PTPN11 to wtRAS, providing the molecular mechanism for the wtRAS activation. Pre-inhibition of RAS or PTPN11, but not of PI3K or JAK-signaling, prevented TSLP-induced RAS-GTP boost. Cytotoxicity assays on primary clinical DS-ALL samples demonstrated that, regardless of mutation status, high-risk leukemic cells could only be killed using RAS-inhibitor or PTPN11-inhibitor, but not PI3K/JAK-inhibitors, suggesting a unified treatment target for up to 80% of DS-ALL. Importantly, protein activities-based principal-component-analysis multivariate clusters analyzed for independent outcome prediction using Cox proportional-hazards model showed that protein-activity (but not mutation-status) was independently predictive of outcome, demanding a paradigm-shift in patient-stratification strategy for precision therapy in high-risk ALL.